Web-Based Logistics Management Information System in CV Anita Ks: Web-Based Logistics Management Information System in CV Anita Ks - Teguh Riyono Adi; Septi Andryana; Ratih Titi Komala Sari (Institute of Computer Science (IOCS), 2020)
The logistics management information system of CV ANITA KS was made because the company is still utilizing a logistical management system made by Microsoft, namely Microsoft Excel, so that the data is still in files and is not neatly stored in the database. This application was made to facilitate the work of logistics administration in managing existing logistics and facilitate monitoring of logistics conditions in the company. This information system application was created using the PHP programming language and using the Mysql database. The design of this application begins with attention to the state of the company and then asks the questions needed to make an overview of how this application will be made, then do the design and manufacture of the system. The system is made with various references obtained, then carried out trials with localhost and run with Firefox browser.